Unravelling the unfolding pathway of human Fas-activated serine/threonine kinase induced by urea. Issue 15 (2nd September 2021) - Alamry, Khalid A.; Srivastava, Saurabha; Shahbaaz, Mohd; Khan, Parvez; Gupta, Preeti; Syed, Sunayana Begum; Azum, Naved; Asiri, Abdullah M.; Islam, Asimul; Ahmad, Faizan; Hassan, Md. Imtaiyaz
Abstract: Fas-activated serine/threonine kinase (FASTK) is a mitochondria-associated nuclear protein that inhibits Fas- and UV-induced apoptosis. This protein is generally activated during Fas-mediated apoptosis by phosphorylating a nuclear RNA-binding protein T-cell intracellular antigen-1 and thus considered as a modulator of apoptosis. In the present study, we have examined the equilibrium unfolding and conformational stability of the kinase domain of FASTK (FASTK353-444 ) . The kinase domain of FASTK353-444 was cloned, expressed, and purified. The folding ↔ unfolding transitions of urea-induced denaturation was monitored with the help of circular dichroism, intrinsic fluorescence, and UV absorption spectroscopies. Analysis of transition curves obtained from different probes revealed a coincidence of denaturation curves, suggesting that folding/unfolding of FASTK follows a two-state process with the midpoint ( C m ) value at 3.50 ± 0.1 M. Urea-induced denaturation curves were further analyzed to estimate change in the Gibbs free energy in the absence of urea (Δ G D 0 ) associated with the equilibrium of denaturation. To get atomistic insights into the urea-induced denaturation of FASTK, we performed an all-atom molecular dynamics simulation for 100 ns. A close agreement was noticed between experimental and computational studies. This study will help to understand the unfolding mechanism and structural stability of the kinase domain of FASTK. Communicated by Ramaswamy H. Sarma